The potential of rapid molecular RT-PCR for SARS-CoV-2 detection: implementation of the Cobas Liat system with urgent patients during a high-incidence season in Thailand - Suwannarat, Pongwut; Tiyasirichokchai, Rawiporn; Rojanasang, Pornparn; Jomoui, Wittaya (Archives of Allied Health Sciences, 2023)
There had been a high incidence of COVID-19 in Thailand between May 2021 and February 2022. Urgent cases in the emergency department (ED) or labor room (LR) should be immediately tested. We aim to implement a rapid molecular point-of-care tests (POCTs) using Cobas Liat for SARS-CoV-2 identification. A total of 32 random leftover-samples represented 100% overall concordance among the 2 POCTs and standard RT-PCR assays. A total of 3,188 nasopharyngeal swabs from an ED and LR were investigated with Cobas Liat system. The incidence of SARS-CoV-2 infection was observed to be 7.53% (164/2,179) in ED and 2.87% (29/1,009) in LR. Furthermore, symptomatic cases were noted in 69.51% (114/164) of ED patients, whereas only one case was recorded from the LR. Finally, this potential strategy could reduce turnaround time and the risk of infection in medical staff during the management of patients or medical procedures in the ED and LR.